Microstructural study of phase separation in (GeS3)100-xAgx and (GeS2)100-xAgx chalcogenide glasses. (2021) - Lishchynskyy, I.; Kaban, I.; Shuleshova, O.; Xi, L.; Jóvári, P.; Stronski, A.; Wagner, T.; Gemming, T.
Abstract: Microstructure of (GeS3 )100-x Agx (x = 0, 5, 10, 15, 20, 25) and (GeS2 )100-x Agx (x = 0, 5, 10, 15, 20) has been studied by scanning electron microscopy. It is found that the glasses of both systems are phase separated: (GeS3 )100-x Agx for 5 ≤ x ≤ 20 at.% and (GeS2 )100-x Agx for 10 ≤ x ≤ 15 at.%. Morphology of coexisting phases is essentially dependent on the glass composition. The phase-separation is very pronounced in (GeS3 )100-x Agx glasses and is diminished in (GeS2 )100-x Agx as indicated by the size and spatial distribution of majority and minority phases.